Classical Biological Control of the Cassava Green Mite - Megevand, B.; Yaninek, J.S.; Friese, D.D. (1987)
A programme to control the cassava green mite (CGM), Mononychellus tanajoa, using classical biological control was initiated in 1983 as part of the Africa-wide Biological Control Programme (ABCP). Basic studies on the field ecology and biotic potential of CGM, and surveys of CGM and associated indigenous natural enemies found on cassava throughout Africa are being used to develop ecologically sound release and follow-up strategies. Applied work includes colony maintenance of exotic phytoseiids, development of methodologies for mass producing, transporting and releasing natural enemies, plus experimental releases and post-release surveys. Important parts of the work are being done in collaboration with several institutes and agencies, including foreign exploration and preliminary screening of exotic natural enemies, international quarantine services, regional release and follow-up surveys, taxonomy of CGM and phytoseiids, simulation modelling of CGM in the cassava ecosystem, artificial diets for transporting CGM natural enemies, survey of entomopathogens of CGM and predatory behaviour studies of exotic phytoseiids.